An Examination of Compound Flood Hazard Zones for Past, Present, and Future Low-Gradient Coastal Land-Margins - Santiago-Collazo, Félix L.; Bilskie, Matthew V.; Bacopoulos, Peter; Hagen, Scott C. (Frontiers in Climate, 2021)
Recent events worldwide demonstrate how coastal communities of integrated natural and human systems are exposed to hydrological and coastal flooding processes. Standard flood hazard assessment practices account independently for rainfall-runoff, tides, storm surge flooding and not the nonlinear combination commonly defined as compound flooding. This research evaluates compound flood hazard zones for past, present, and future (c. 1890 – 2090) conditions of the Mississippi River Delta Plain (MRDP). The MRDP provides a low-gradient coastal land-margin representing similar landscapes around the world that are experiencing relative sea-level rise and serves as a warning beacon for our coastal settlements. A set of plausible synthetic storms and rainfall events, which account for antecedent rainfall-runoff, tropical cyclone-driven rainfall, and tropical cyclone-driven surge, are employed in a tide and surge hydrodynamic model that integrates rain over the mesh. This study demonstrates the evolution of the compound flood hazard zones from the 1890s, before major western settlement and alterations to the Mississippi River and deltaic system, to the present day and out to 2090. Furthermore, near-future projections of the compound flood hazard zones suggest that the coastal flood zone will suffer the most significant changes in coverage area due to a combination of increasing eustatic sea-level rise, high-frequency flood events, and alterations to the coastal land-margin. Our results emphasize the need to establish evolution trends of compound flood hazard zones to enable more descriptive future projections under a changing climate. Such projections will aid policy-makers, stakeholders, and authorities as they pursue enhanced coastal resilience to compound flooding.